259. A Retrospective Cross-Sectional Comparison of the Neonatal Gut Microbiota After Antimicrobial Exposure: Implications for Stewardship. (26th November 2018) - Rooney, Ashley; Coburn, Bryan; Science, Michelle
Abstract: Background: The development of the infant gut microbiota influences the maturation of the host immune system and has been implicated in both short- and long-term health outcomes. In a healthy infant, the initial stages of gut microbiota development are characterized by the progressive acquisition and proliferation of anaerobes. In the neonatal intensive care unit (NICU), infants are often exposed to antibiotics which disturb the normal development of the gut microbiota. In this retrospective cross-sectional study, we aimed to the evaluate the effects of three different antibiotic regimens on the gut microbiota of infants in the NICU, focusing on the effect on anaerobe colonization. Methods: From November 1, 2014 to April 30, 2015, stool swabs were collected from NICU patients at The Hospital for Sick Children. Infants were included in the study if they received any dose or duration of the following antibiotics: ampicillin and tobramycin (AT), ampicillin and cefotaxime (AC), or ampicillin, tobramycin, and metronidazole (ATM). DNA was extracted from stool swabs and subject to Illumina sequencing of the V4 hypervariable region of the 16S rRNA gene. Infants were stratified by gestational age (term or preterm). The first samples taken within 1 week after antibiotic exposure were analyzed for diversity measures, taxonomic composition, and anaerobe relative abundance. Results: A total of 64 NICU infants were included in the study, 46 (71.9%) received AT, 7 (10.9%) received AC, and 11 (17.2%) received ATM. Term infants received either AT (19/46; 41.3%) or AC (7/7; 100%), whereas preterm infants received either AT (27/46; 58.7%) or ATM (11/11; 100%). Shannon diversity was not statistically significant between term infants receiving AT and AC or preterm infants receiving AT and ATM. However, the relative abundance of anaerobes was significantly decreased after exposure to ATM in comparison to preterm infants receiving AT ( P < 0.005) Conclusion: Within 1 week after ATM therapy, the relative abundance of gut anaerobes in preterm infants were significantly decreased in comparison to preterm infants receiving a course of AT. Therefore, limiting the use of ATM in preterm infants may protect the developing gut microbiota. Disclosures: All authors: No reported disclosures.